1991
DOI: 10.1002/anie.199108541
|View full text |Cite
|
Sign up to set email alerts
|

Triple Inclusion by a Calixarene: the CrystaL Structure of the Europium(III) Complex of Bis(homooxa)‐p‐tert‐butylcalix[4]arene

Abstract: 41 a) 1 crystallizes monoclinically, P2,/c; a = 12.465(1), b = 15.786(1), c = 17.629(2) A, B = 96.62(1)", Z = 4, 5039 independent reflections (Mo,,: 1.5" I 0 I 25.0"), 3651 observed with 1 2 2 4 0 ; 343 parameters, R = 0.064, Rw = 0.078 [4d]; b) 2: P2,/n; a = 13.019(2), b = 17.586(3), c = 18.557(3)A, / 3 = 106.62(1)", Z = 4, 4751 independent reflections (Mo,, 0.5" I 0 I22.5") 3981 observed with 1 2 241); 424 parameters, R = 0.045, R , = 0.055 [4d]; c) 3: triclinic, Pi; a = 12.724(8), b = 2 = 2, 5690 independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 8 publications
1
40
0
1
Order By: Relevance
“…The macrocyclic ligand in the complex has a cup form each of which includes a DMSO molecule. The structure of the complex is similar to that of the dimer complex of monooxacalix [4]arene 37 with Eu [35].…”
Section: Receptor Properties Of Hexahomotrioxacalix[3]arenes With Frementioning
confidence: 74%
“…The macrocyclic ligand in the complex has a cup form each of which includes a DMSO molecule. The structure of the complex is similar to that of the dimer complex of monooxacalix [4]arene 37 with Eu [35].…”
Section: Receptor Properties Of Hexahomotrioxacalix[3]arenes With Frementioning
confidence: 74%
“…n DMSO, 14 as reported previously for the synthesis of lanthanoid calixarene complexes. 9,[15][16][17] Reaction of these solvates with pytz and triethylamine in organic solvents resulted in the unexpected crystallisation of hydrates, confirmed by the structural characterisation of [Eu(pytz)3(H2O)3]. Decreasing the metal:ligand ratio resulted in the crystallisation of the novel system [Y(pytz)2(H2O)4](pytz).…”
Section: Hpytzmentioning
confidence: 90%
“…The inclusion of two chemically different solvent molecules in a calixarene cavity is a somewhat uncommon feature, at least for small calixarenes [in both compounds (II) and (III), two identical molecules were included, acetonitrile in (II), pyridine in (III)]. It has been suggested that the ability of calixarenes to hold two different species relatively close one to the other was indicative of their potential as`enzyme mimics' (Asfari et al, 1991). The location of the chloroform H atom is indicative of a possible hydrogen bond with the O atom of tetrahydrofuran.…”
Section: Commentmentioning
confidence: 99%